A leitura como melancolia: memória, presente e vazio na crítica de José Castello - Oliveira, Ana Paula de (2020)
This research aims to understand José Castello's way of reading, based on the analysis of the text Uma defesa da melancolia (2013), published in the Prosa section of the newspaper O Globo, in his weekly column called A literatura na poltrona, from the assumption that Castello reads remembering, or even, he reads in a melancholic way, and that, like him, we may read the same way. In other words, we start from the premise that we carry out a reading movement similar to the critic’s, which seems to be built based on the relationship between actuality and memory, voluntary and involuntary, and that such reminiscences establish an emptiness in the present of this subject. First, the work takes place through analysis, description, criticism and the investigation of other meanings of the melancholy metaphor, which appear throughout the text, from the contributions of Giorgio Agamben (2007), José Castello (2007), Michel Pêcheux (2008) and Walter Benjamin (1989). Then, we tried to observe the historicity of melancholy, through its slips such as emptiness / lack, poetry / melancholy and shadow / inexplicable light, through Gerry Maretzki (2010), Giorgio Agamben (2007), Sigmund Freud (2011) and Walter Benjamin (1984), in order to understand, anachronically, the paradoxical character of this affection, from its origin. Finally, we ware concerned to think about reading as melancholy from the perspective of Giorgio Agamben (2009), Georges Didi-Huberman (2017), Marcel Proust (2017), Michèle Petit (2009) and Roland Barthes (2004). In other words, it was a question of analyzing the discursiveness of this reading gesture, based on the dialectic between past and present, and how this reading occurs, which occurred between two times, whose encounter causes a rupture, a confluence from which, we think, a melancholic way of reading is born.